EDUKASI PERILAKU SEHAT BAYI DAN BALITA DIMASA PANDEMI COVID-19 PADA KADER AISYIYAH TANJUNG - Wulan Margiana; Ima Syamrotul; Khamidah Achyar (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2022)
Signs and symptoms of COVID-19 in children are difficult to distinguish from respiratory disease due to other causes. Symptoms can include cough and cold like the common cold or flu, with or without fever, which is generally mild and will resolve on its own. Respiratory tract disease becomes dangerous if it attacks the lungs, which becomes pneumonia or what is called pneumonia. Symptoms of pneumonia are fever, cough, and difficulty breathing which is characterized by rapid breathing and shortness of breath. Data on the incidence of COVID-19 in children under five is not sufficient, but one journal states that cases of COVID-19 at the age of 0-9 years in China are 0.9%, South Korea is 1% and Italy is 0.6%. This activity aims to find out knowledge about the healthy behavior of infants and toddlers during the Covid-19 pandemic in Aisyiyah Tanjung cadres. The method used at IbM offered to Mitra Aisyiyah Tanjung is counseling to cadres using the learning by doing method. The results of the pre and post tests showed an increase in the knowledge of cadres about education on healthy behavior for infants and toddlers during the Covid-19 pandemic. The conclusion is that there is an increase in knowledge of Posyandu Aisyiah Tanjung cadres.